Differences in Steaming Temperatures of Gambir Tanned Eco Printing Sheepskin on Physical Quality, Colour Fastness, and SEM - Andipratama, Brian; Pertiwiningrum, Ambar; Abidin, Mohammad Zainal (Faculty of Animal Science Universitas Brawijaya, 2025)
This study aims to evaluate the quality and microscopic structure of sheepskin that has undergone a tanning process using natural tannins in the form of gambir. This study used sheepskin that had been tanned and subjected to four ecoprint steaming temperature treatments: no steaming (P0), 50°C (P1), 60°C (P2), and 70°C (P3). The evaluation of tanned sheepskin was carried out by measuring tensile strength, elongation, tear strength, softness, shrinkage temperature, and SEM (Scanning Electron Microscopy). The data obtained were analyzed using the One Way Anova test. If the results were significantly different, they were followed up with a DMRT test. The results showed that all parameters showed significant differences (p < 0.05) between treatments. The steaming treatment at 60°C showed the best results in terms of tensile strength, tear strength, and collagen fiber structure compactness as observed by SEM. The collagen fiber structure in the skin appeared denser and the pores were more evenly distributed compared to the other treatments. From the results of the study, it can be concluded that steaming temperature plays a crucial role in the physical quality of sheepskin. These findings suggest that controlled evaporation can improve ecological print results and support sustainable leather processing.